PERLINDUNGAN HUKUM TERHADAP ANAK DIBAWAH UMUR DARI JUDI ONLINE BEDASARKAN UNDANG-UNDANG PERLINDUNGAN ANAK - Fahrudin, Irvan; Shodiq, MD; Ismed, Mohamad (SINERGI : Jurnal Riset Ilmiah, 2026)
Online gambling can be categorized as a cybercrime,because its criminal acts are carried out using the internet and computers. The occurrence of online gambling stems from the misuse of technological advancements, where gambling is conducted without face-to-face interaction and can instead be done online. Moreover, its payment transactions can be made via bank transfer, which makes it difficult for law enforcement officers to trace the perpetrators of online gambling. The victims of online gambling are not only adults and the elderly, but also include children. Children themselves are national assets that must be nurtured and protected by both the government and the law. In this regard, the author establishes the main issue, namely: The form of legal protection for children and the implementation of child protection laws to achieve justice and protect children from online gambling. For this thesis, the author uses a normative legal research method, which focuses more on written legal rules and the applicable system of norms, such as legislation and legal doctrines. This method examines how the law should be applied based on existing legal norms and principles, rather than how the law is actually implemented in society (a normative–empirical study).